2017
DOI: 10.1039/c6cc08492c
|View full text |Cite
|
Sign up to set email alerts
|

A red-NIR fluorescent dye detecting nuclear DNA G-quadruplexes: in vitro analysis and cell imaging

Abstract: Light-up of nuclear G-quadruplex DNA in cells by an aggregating and red/NIR emitting dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…Thel ogical conclusion is that this nucleolar staining results from ligand binding to nucleic-acid G4 targets. [11] As fixation protocols may lead to drug relocalization and artefacts, [18] we repeated this experiment but with cell fixation before drug incubation;identical results were obtained (see Figure S11 B), thus confirming that the staining pattern was not influenced by our protocol.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Thel ogical conclusion is that this nucleolar staining results from ligand binding to nucleic-acid G4 targets. [11] As fixation protocols may lead to drug relocalization and artefacts, [18] we repeated this experiment but with cell fixation before drug incubation;identical results were obtained (see Figure S11 B), thus confirming that the staining pattern was not influenced by our protocol.…”
supporting
confidence: 70%
“…[10] However,o ther studies demonstrated the localization of G4 ligands mostly in anuclear substructure called the nucleolus, the multifunctional domain in which ribosome biogenesis takes place. [11] This localization is consistent with the existence of numerous quadruplex-forming sequences in ribosomal DNA( rDNA), which is particularly rich in Ga nd C residues,a nd with the high level of transcriptional activity in the nucleolus involving noncanonical DNAa nd RNAs tructures,which may together constitute ideal targets for this class of molecule.H owever,i th as been difficult to demonstrate conclusively that G4-ligand accumulation in the nucleolus is guided specifically by quadruplexes,a st his subcompartment has been shown to trap drugs with surprisingly diverse structures,i ncluding DNAi ntercalators,a nticancer agents, RNAd yes,m etallic complexes,a nd cell-penetrating peptides. [12] Thes pecificity and relevance of the nucleolar localization of G4 drugs therefore remain open questions in the particular context of quadruplex structure recognition.…”
supporting
confidence: 68%
“…While RNase treatment did not modify CQ4 nucleolar staining, the nucleolar ThT signal was reduced by the presence of the enzyme, indicating the ability of CQ4 to preferentially target DNA G4 structures. DNase treatment was not performed due to the apparent inability of this enzyme to reach the nucleoli . Instead, DNA G4 binding was confirmed by using the well‐known G4‐binder Phen‐DC 3 (Figures C and Supporting Information, Figure S47).…”
Section: Resultsmentioning
confidence: 99%
“…However, upon binding to G4, the equilibrium shifts as a result of the local hydrophobic environment, through intercalation, allowing the NDIs to be present in the fluorescent monomeric forms. Interestingly, these red/near‐IR compounds are highly selective to G4 with respect to dsDNA with rapid cellular entry . These molecules are good application examples through modulating solvent solubility, tuning brightness through core‐substitution and further derivatisation to introduce other functional motifs.…”
Section: Core‐substitutionmentioning
confidence: 99%
“…Interestingly,t hese red/near-IR compounds are highly selective to G4 with respectt o dsDNA with rapid cellulare ntry. [25] These molecules are good application examples through modulating solvent solubility, tuning brightness through core-substitution and furtherderivatisationtoi ntroduce other functional motifs.…”
Section: Secondary Cyclic Arylaminesmentioning
confidence: 99%